2006
DOI: 10.1002/nbm.1016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a decision support system for diagnosis and grading of brain tumours using in vivo magnetic resonance single voxel spectra

Abstract: A computer-based decision support system to assist radiologists in diagnosing and grading brain tumours has been developed by the multi-centre INTERPRET project. Spectra from a database of 1 H single-voxel spectra of different types of brain tumours, acquired in vivo from 334 patients at four different centres, are clustered according to their pathology, using automated pattern recognition techniques and the results are presented as a two-dimensional scatterplot using an intuitive graphical user interface (GUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
331
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(348 citation statements)
references
References 33 publications
16
331
0
1
Order By: Relevance
“…Potential roles have been identified in pre-surgical diagnosis of tumour type and grade (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), monitoring of treatment response (20), and evaluation of tumour recurrence (21). However, optimised MRS analysis is required to enable the widespread clinical use of the technique.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Potential roles have been identified in pre-surgical diagnosis of tumour type and grade (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), monitoring of treatment response (20), and evaluation of tumour recurrence (21). However, optimised MRS analysis is required to enable the widespread clinical use of the technique.…”
mentioning
confidence: 99%
“…However, optimised MRS analysis is required to enable the widespread clinical use of the technique. Pattern classification of MRS data alone or in combination with MRI features has proven successful for accurately classifying brain tumours (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although brain tumours are the most common solid tumours in children and a major cause of childhood mortality, they are rarer than in adults, and only small numbers have been reported in the few studies using MRS to discriminate paediatric brain tumours (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 For this reason, the features containing little discriminative power must be discarded, which means that we will need a large number of cases (about three to five times more cases than the number of features to extract) from which to extract those features. 7,8 However, in real life, the number of available cases will be limited by epidemiology and budget. This problem is called the curse of dimensionality.…”
Section: How Many Data?mentioning
confidence: 99%
“…The aim of this project is to help improve brain tumour classification by providing alternative, non invasive techniques. A predecessor project, Interpret [7], has shown that MRI and single voxel MRS data can aid in improving brain tumour classification. HealthAgents builds on top of these results and further employs multi voxel MRS data, as well as genomic DNA micro-array information for better classification results.…”
Section: Introductionmentioning
confidence: 99%